2005
DOI: 10.1007/s10897-005-1159-6
|View full text |Cite
|
Sign up to set email alerts
|

Women's Attitudes Toward Testing for Fragile X Carrier Status: A Qualitative Analysis

Abstract: Fragile X syndrome (FXS) is primarily due to a repeat expansion mutation found in the FMR1 X-linked gene. We have conducted a qualitative analysis of responses from women concerning their attitudes toward testing for carrier status of the fragile X mutation among reproductive-age women. We obtained responses from focus groups including women with and without FXS in their families. We found the following themes: (1) mothers of children with FXS have difficulty formulating their opinions on population screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Awareness of FXS is considered low in the general community (Anido et al 2005;Anido et al 2007;Archibald et al 2009;Fanos et al 2006;Metcalfe et al 2008). There have been only two reports measuring women's knowledge of FXS who were offered testing.…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…Awareness of FXS is considered low in the general community (Anido et al 2005;Anido et al 2007;Archibald et al 2009;Fanos et al 2006;Metcalfe et al 2008). There have been only two reports measuring women's knowledge of FXS who were offered testing.…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…26 A few studies have examined the attitudes of participants toward being screened, either within a testing protocol [27][28][29] or in the absence of offering testing. 30 However, there have been little published data describing decision-making and psychosocial consequences of such screening in women with no family history of FXS. Only in one small study of 20 women was there an attempt to evaluate whether participants made an informed decision to be tested.…”
mentioning
confidence: 99%
“…Participants were unanimous in their views that individuals with test-positive results arising from FXS carrier screening should be provided with genetic counseling which is consistent with current recommendations (Finucane et al 2012;McConkie-Rosell et al 2007). Research indicates that individuals identified as carriers through population screening may differ in their genetic counseling needs compared with individuals who have a personal or family history of FXS, as they may be relatively unprepared for a carrier result (Anido et al 2005(Anido et al , 2007 and may have very limited knowledge and prior experience of FXS (Archibald et al 2009). Thus, clear pathways for referral for carriers should be an integral component of any FXS screening program and genetics services should have protocols for coordinating the management of individuals identified through population screening programs and their families .…”
Section: Discussionmentioning
confidence: 71%
“…Data were collected through semistructured interviews and focus groups using questions developed by drawing on published qualitative research in this area (Anido et al 2005(Anido et al , 2007 and our prior research outcomes (Metcalfe et al 2008;Metcalfe and Archibald 2012). Topics included general questions about awareness of genetic conditions, genetic screening, and FXS; perceptions of factors that might influence decision-making about carrier screening, perceived benefits, and concerns about carrier screening; views on whether population-based carrier screening should be available to all women; and when and where FXS carrier screening could be offered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation